Initial hepatic artery infusion and systemic chemotherapy for asymptomatic colorectal cancer with un-resectable liver metastasis - Shi, Liangrong (Int J Clin Exp Med, 2015)
Purpose: Hepatic arterial infusion (HAI) has been proved to be an effective strategy to increase the chances of resection for colorectal cancer patients with liver metastasis (CRCLM). Herein, we aimed to evaluate the benefits and risks of initial treatment with HAI floxuridine (FUDR) and systemic XELOX in un-resectable synchronous CRCLM. Materials and methods: HAI catheter systems were implanted radiologically in 54 patients with un-resectable synchronous CRCLM. Upfront HAI FUDR and systemic XELOX were delivered without primary cancer resection. Patients underwent deferred surgery when the metastatic diseases were converted to resectability, or any serious colorectal cancer-related complications occurred. Results: Thirty-eight patients (70.4%) were converted to resectability and underwent staged or synchronous resection of the primary tumor and metastatic disease, with an estimated 3-year survival rate of 76% compared with 15% in un-resected patients. Uni-variate analysis showed that hepatic involvement, number of lesion, and the location of primary cancer did not affect resectability rate. Only 3 patients (5.6%) required palliative surgery to treat complications related to primary cancer. Conclusions: Initial HAI FUDR and systemic XELOX are effective to help patients with CRCLM to obtain a high resection rate for asymptomatic colorectal cancer and un-resectable liver metastases, and associated with a low rate of complications related to the intact primary cancer.